Formulation and Characterization of Paracetamol, Diclofenac Sodium and Domperidone Lozenges - S. Rahath Fathima (International Journal of Allied Medical Sciences and Clinical Research, 2020)
A combination of paracetamol, diclofenac and domperidone were formulated in the lozenge form to make available the immediate release of the drugs in fever, pain and nausea conditions. Lozenges are a form of dosage forms that deliver the drug in the oral cavity. They dissolve slowly in the mouth to release the medicament. A number of dosage forms like tablets, syrups, capsules are available for the above stated drugs but none acts locally and effectually. The aim of current investigation is to prepare the medicated lozenges of paracetamol, diclofenac and domperidone and to evaluate the same to meet the needs of increased bioavailability and reduced hepatic toxicity and gastric irritation. Lozenges were prepared by heat congealing method with varying concentrations of sugar base and polymer. Formulated lozenges were evaluated for various physicochemical parameters like hardness, weight variation, moisture content, friability and invitro dissolution. The results obtained were compared with pharmacopoieal limits. FTIR studies revealed no signs of incompatibility between the drugs and its excipients. Hardness, friability, moisture content of the prepared lozenges were found within the limits. Invitro dissolution studies showed the drug release of 90% at the end of 30 minutes. Thus, it can be concluded that medicated lozenges are suitable for large doses and immediate drug release requirements with improved bioavailability